Cervantes Virtual Centre (Journal of Parents and Teachers, 2014)
An article about online resources of the Instituto Cervantes. The website is divided into four sections: the teaching section, the literature section, the language section and the arts section. In all of them we can find games, pastimes and online exercises to learn and practice with the Spanish language.
Keywords: website; Spanish as a foreign language; hispanic literature; online resources.